HUBUNGAN TEKANAN PANAS, BEBAN KERJA DENGAN KELELAHAN KERJA PADA TENAGA KERJA DI PT. KERETA API UPT. BALAI YASA YOGYAKARTA - , Hasanudin, SKM, Dr.dr. Lientje Setyawati Maurits, MS, Sp.OK ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: an uncomfortable hot workplace may impact to its workers, such as affecting their blood pressure, pulse, additional workload and exhaustion. Some factors affect the exhaustion are physical work and workload. This study was conducted at PT. Kereta Api UPT. Balai Yasa Yogyakarta which located on Kusbini Street No. 1 Kecamatan Demangan Yogyakarta. Study purpose: the purpose of this study was to determine effect of temperature workplace, workload toward occupational exhaustion of workers of PT. Kereta Api UPT. BalaiYasa Yogyakarta. Study method: this is a cross sectional. The sample in this study was 43 respondents. The independent variable was hot workplace and workload while the dependent variable was occupational exhaustion. The analysis used in this study was Pearsonâs Product moment to test the effect of hot workplace, workload toward occupational exhaustion. Study result: the testing result of sample analysis from Kolmogorov Smirnov Test yielded that temperature workplace p=0,248, workload p=0,571 and occupational exhaustion p=0,478, so, it is determined the three variables was normally distributed. For test result of Pearson Moment Product, it yielded hot workplace of value p=0.200 (p>0.05) which shown there no effect found between temperature workplace with occupational exhaustion experienced by the workers of PT. Kereta Api UPT. Balai Yasa Yogyakarta, while the workload was gained value p=0.041. Since value p<0.05 it means existed effect of workload with occupational exhaustion toward the workers of PT. Kereta Api UPT. Balai Yasa Yogyakarta. The test result of linear regression of both variables resulted R Square of 0.445. It shows the contribution value of workload toward increase of occupational exhaustion of 44.5%, whereas the remained 55.5% caused by other factors. Conclusion: there existed a significant effect between workload with occupational exhaustion of the workers at railway workshop of UPT. Balai Yasa Yogyakarta. It was no found a significant effect between temperature workplace toward occupation exhaustion, presumably due all workers of metal division of PT. Kereta Api UPT. Balai Yasa Yogyakarta has worked for more than 5 years which acclimated toward their occupational workplace.